LEMBAGA KEUANGAN MIKRO DI INDONESIA - Baskara, I Gde Kajeng (Buletin Studi Ekonomi; VOL.18.NO.2.AGUSTUS 2013. (PP 85-190), 2014)
Abstract : Microfinance Institutions in Indonesia. Microfinance institutions is one of the pillars in the financial intermediation process. Microfinance is needed by the poor for either consumption or production, and also for saving activities. The aim of this article were describes how the existence of microfinance institutions in Indonesia and analysis of existencies this institution from the view of new regulation (Undang undang nomer 1 tahun 2013 tentang lembaga keuangan mikro) . The presentation of this article is divided into four main themes: (1) the concept and definition of microfinance, (2) the historical of microfinance institutions in Indonesia, (3) microfinance institutions that currently exist in Indonesia, and (4) review of Undang-undang nomer 1 tahun 2013 tentang lembaga keuangan mikro, the regulation of microfinance institution in Indonesia . The results of this article discussion shows that wide variety types of microfinance institutions in Indonesia is based on the heterogeneity of the community. Regulations and legality is needed to strengthen the role of this institution The study of Indonesian microfinance were expected to broaden our insights about the role of these institutions in the development process and the concept of future development.
Keywords: microfinance, microfinance institution, history of Indonesian microfinance